THE RELATIONSHIP BETWEEN TEACHERS' PERCEPTION TOWARDS THEIR LEADERSHIP CAPACITY AND THEIR CLASSROOM MANAGEMENT STYLES IN THE SECOND AFFILIATED MIDDLE SCHOOL OF YUNNAN NORMAL UNIVERSITY, CHINA - WANG, PEIRAN; VINITWATANAKHUN, WATANA (Scholar: Human Sciences, 2022)
This study aimed to survey 80 full-time lecturers in selected schools for the 2020 school year (September to January). The main data collection tool is a questionnaire divided into three parts. The relationship between these two variables is analyzed using the mean and standard deviation. The research results show that the summary of means and standard deviations of teachers’ perception towards their leadership capacity. The total mean score was 2.86 in the range of 2.51-3.50 and is interpreted as Good enough. And the research results show that the total mean score of teachers’ classroom management styles was 2.84, and it was in the range of 2.51-3.50. According to the criteria of the interpretation, teachers’ perceptions of classroom management styles were Moderate. Pearson Product Moment Correlation Coefficient was applied to test in this study, Pearson correlation was -.152 and Sig was .001. Which indicated that there was a weak negative relationship between teachers’ perception towards leadership capacity and classroom management styles at Second Affiliated Middle School of Yunnan Normal University, China.